2004
DOI: 10.3406/estat.2004.7247
|View full text |Cite
|
Sign up to set email alerts
|

Mesurer les préférences individuelles à l'égard du risque

Abstract: [eng] Measuring Individual Time Preferences . Microeconomic theory makes a saver’s choices dependent on the lifecycle of his discount rate, or on the subjective discount rate he uses to anticipate his future gratifications. The higher this rate, the lower the savings level. This time preference, characteristic of the agent’s life expectancy, needs to be differentiated from the parameters that govern his decisions as regards other timeframes: his extent of shorter-run impatience, but also his intergenerational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
4
1
1
Order By: Relevance
“…We do not find any correlation between age and risk aversion, contrary toBarksy et al (1997),Arrondel et al (2004) andKapteyn and Teppa (2011). This may be due to the fact that we restricted the age of our respondents to be comprised between 40 and 60.…”
contrasting
confidence: 92%
See 2 more Smart Citations
“…We do not find any correlation between age and risk aversion, contrary toBarksy et al (1997),Arrondel et al (2004) andKapteyn and Teppa (2011). This may be due to the fact that we restricted the age of our respondents to be comprised between 40 and 60.…”
contrasting
confidence: 92%
“…They also find that whites are more risk averse than blacks, while hispanics are the least risk averse. Arrondel et al (2004), using French data, find that risk aversion is increasing with age but decreasing in income and in education. 19 In both studies, males are found to be less risk averse.…”
Section: Frequency Of Deviation From Risk Neutralitymentioning
confidence: 99%
See 1 more Smart Citation
“…We took inspiration from various authors to design psychometric questionnaires (Barsky et al, 1997;Weber et al, 2002;Malhotra, 2006;Abdellaoui et al, 2007;Arrondel et al, 2004).…”
Section: Designing a Bias-free Questionnairementioning
confidence: 99%
“…Autrement dit, il semble que les garçons s'affi rment par leur look sans trop craindre les résultats de leurs choix, tandis que les fi lles, moins entreprenantes, sont plus sensibles aux effets sociaux de l'apparence. Ce résultat pourrait être rapproché du fait, bien documenté (Arrondel, Masson et Verger, 2004), que les hommes ont une plus faible aversion pour le risque que les femmes. Les hommes affi rmeraient plus facilement un look parce qu'ils redoutent moins que les femmes les possibles conséquences négatives de cet affi chage identitaire.…”
Section: Garçonsunclassified